The Dark Side of Relational Leadership: Positive and Negative Reciprocity as Fundamental Drivers of Follower’s Intended Pro-leader and Pro-self Unethical Behavior - Vriend, Tim; Said, Ramzi; Janssen, Onne; Jordan, Jennifer (Frontiers in Psychology, 2020)
In this study, we use a social exchange perspective to examine when (i.e., high- vs low-quality leader-member exchange [LMX]), why (i.e., positive vs. negative reciprocity), and how (i.e., pro-leader vs. pro-self unethical behavior) followers consider unethical behavior that either benefits the leader or the self. Across an experimental and a time-split survey study, we find that high-quality LMX relationships motivate pro-leader unethical intention as a means to satisfy positive reciprocity motives, and that low-quality LMX relationships motivate pro-self unethical intention as a means to satisfy negative reciprocity motives. Importantly, our studies demonstrate that it is crucial to incorporate both positive and negative reciprocity motives when studying effects of LMX. Implications of these results for social exchange theory, leader-member exchange, and the broader literature of (self- and other-serving) unethical behavior are discussed.